A novel approach for global environmental performance evaluation of electric batteries for hybrid vehicles. (10th July 2017) - Garcia, Julien; Millet, Dominique; Tonnelier, Pierre; Richet, Sophie; Chenouard, Raphaël
Abstract: The automotive product is increasingly restricted by environmental regulations, including reducing emissions of CO2 and pollutants in exhaust pipes of vehicles. One solution implemented in the automotive industry are plug-in hybrid electric vehicles (PHEV) that use an electric traction battery. To help vehicle manufacturers in their choice of traction battery from an environmental point of view, a simulation method of environmental impacts generated by the use phase is proposed in this paper. This method takes into account the possible usages of the vehicle and potential developments of electric mix, with the formulation of a constraint satisfaction problem (CSP) solved using constraint programming (CP) techniques. The sensitivity of five parameters is investigated: the electricity mix used to charge the battery, the battery mass, electric consumptions, the autonomy in "all-electric mode", and the share of total travel in "all-electric mode". Power grid is the most differentiating parameter for global warming and PHEV generates less impact if less used in "all-electric mode" on a high carbon intensity power grid. Lastly, CSP acausal modeling makes it possible to process different simulations with the same model.